From the extreme to the mean: Acceleration and tipping points of coastal inundation from sea level rise - Sweet, William V.; Park, Joseph (Earth's future, 2014)
Relative sea level rise (RSLR) has driven large increases in annual water level exceedances (duration and frequency) above minor (nuisance level) coastal flooding elevation thresholds established by the National Weather Service (NWS) at U.S. tide gauges over the last half‐century. For threshold levels below 0.5 m above high tide, the rates of annual exceedances are accelerating along the U.S. East and Gulf Coasts, primarily from evolution of tidal water level distributions to higher elevations impinging on the flood threshold. These accelerations are quantified in terms of the local RSLR rate and tidal range through multiple regression analysis. Along the U.S. West Coast, annual exceedance rates are linearly increasing, complicated by sharp punctuations in RSLR anomalies during El Niño Southern Oscillation (ENSO) phases, and we account for annual exceedance variability along the U.S. West and East Coasts from ENSO forcing. Projections of annual exceedances above local NWS nuisance levels at U.S. tide gauges are estimated by shifting probability estimates of daily maximum water levels over a contemporary 5‐year period following probabilistic RSLR projections of Kopp et al. (2014) for representative concentration pathways (RCP) 2.6, 4.5, and 8.5. We suggest a tipping point for coastal inundation (30 days/per year with a threshold exceedance) based on the evolution of exceedance probabilities. Under forcing associated with the local‐median projections of RSLR, the majority of locations surpass the tipping point over the next several decades regardless of specific RCP. Key Points Nuisance coastal flooding is increasing along U.S. coastlines Event rates accelerate as water level distributions exceed elevation thresholds Tipping points for coastal inundation are surpassed in the coming decades